Thoracic spine extension mobility in young adults: Influence of subject position and spinal curvature - Edmondston, S.; Waller, Rob; Vallin, P.; Holthe, A.; Noebauer, A.; King, E. (2011)
TTSTUDY DESIGN: Cross-sectional study. TTOBJECTIVES: To examine extension mobility of the thoracic spine in young, asymptomatic adults, with particular reference to the influence of subject position and magnitude of the thoracic kyphosis. TTBACKGROUND: Impairment of thoracic extension motion is commonly associated with mechanical pain disorders in this region of the spine. Knowledge of normal thoracic mobility and the factors that may influence this motion is important in the evaluation and management of thoracic pain disorders. TTMETHODS: In 40 asymptomatic adults, the total and regional thoracic extension range of motion was measured using 2-dimensional photographic image analysis. Extension mobility was measured in standing, sitting, prone, and 4-point kneeling. The association between the magnitude of the habitual thoracic kyphosis and extension mobility was also examined. TTRESULTS: When measured from the habitual standing position, the mean range of flexion was 11.5° (3.7°) and mean extension range was 8.7° (3.7°). Thoracic extension was significantly greater in unloaded positions compared to loaded positions (P<.001). The standing thoracic kyphosis angle was significantly correlated with the end range thoracic extension angle in all positions (r = 0.63-0.79, P<.001). There was a poor correlation between the thoracic kyphosis angle and thoracic extension range of motion in all positions (r = 0.11-0.34, P>.06). TTCONCLUSION: When measured from the habitual standing position, thoracic extension range of motion in young individuals is small and poorly correlated with the magnitude of the standing thoracic kyphosis. Unloaded positions (4-point kneeling and prone), compared to positions that load the spine (standing and sitting), appear to promote a greater range of thoracic extension motion.